The Impact of Bilateral Investment Treaties on Foreign Direct Investment in Iraq; Facilitation of Internal Reforms - Othman, Arez Mohammed Sediq; Hassan, Ahmed Aziz (Sulaimani Journal for Humanities, 2025)
After the collapse of Saddam regime, the country has been opened toward foreign investors to invest their capitals in Iraq. However, the legal barriers were still stand before investors, as the legal system required major amendments to be conducted to attract foreign investors. In terms of international agreements, Iraq needed a radical reform to rejoin international community and cope with the rapid changes. Bilateral investment treaties were necessary to prepare a proper ground for foreign investors before they really dig in into the investment environment in Iraq. In the recent years, both Federal Government and Kurdistan Regional Government of Iraq had made legal attempts to adopt investment laws aiming to facilitate investment for the foreign investors. In general, both legislations (Kurdistan Regional Government and Federal Government) include provisions encourage foreign investment. This paper discusses that having proper legislations is not the only impetus for foreign investment in the country, but rather having international treaties to back the activities of the investors alongside providing more protection to the foreign investors. Further, the paper will also investigate the role of internal reform to attract foreign investors.
Keywords: Bilateral Investment Treaties; Foreign Direct Investment; Investment Law in Iraq; Investment Law in Kurdistan Region of Iraq; Foreign Investor Protection